From the Editor-in-Chief - Bakar, Osman (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This issue of Katha contains five articles on a wide range of topics written by scholars and academics from different parts of the world. As a journal published by the Center for Civilizational Dialogue dedicated to the pursuit and advancement of intercultural and inter-civilizational dialogue concerning cross-cultural human problems in all their dimensions, Katha tries as far as possible to publishe articles pertinent to these issues.